Molecular Diagnosis and Haemato-biochemical Alteration in Canine Parvoviral Infection in Dogs - Zope, Piyush S; Waghmare, Sunil P; Pajai, Kishor s; Dighe, Dhananjay G; Hajare, Sunil W; Kamdi, Bhupesh P (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was undertaken to diagnose and assess the haematological & biochemical alteration in parvoviral gastroenteritis in dogs. Total of 12 dogs suspected for parvovirus infection were diagnosed by using lateral flow-based immunochromatographic assay rapid canine parvovirus (CPV) antigen test kit and polymerase chain reaction (PCR) technique in the faeces of affected dogs. All 12 dogs were found positive by a rapid antigen test kit and VP2 gene of CPV PCR assay using the CPV-2ab primer pair and expected size of 681 bp. The haemato-biochemical study revealed a decrease in Hb, TEC, serum total protein, albumin and globulin, whereas the increase in absolute neutrophil count and BUN in parvovirus-infected dogs, indicated anemia and hypoproteinemia in parvovirus infected dogs.